Critical roles of rare species in the anaerobic ammonium oxidizing bacterial community in coastal sediments - Yu Zhang; Mingming Chen; Rui Du; Ehui Tan; Shuh-Ji Kao; Yao Zhang (Marine Life Science & Technology, 2025)
Anaerobic ammonium oxidation (anammox) plays a critical role in nitrogen loss in estuarine and marine environments. However, the mechanisms underlying the formation and maintenance of the anammox bacterial community remain unclear. This study analyzed the anammox bacterial diversity, community structure, and interspecific relationships in three estuaries along the Chinese coastline —the Changjiang Estuary (CJE), the Oujiang Estuary (OJE), and the Jiulong River Estuary (JLE) — as well as the South China Sea (SCS) to elucidate their community assembly mechanisms. The results indicated that the anammox bacterial community exhibited the highest ammonium concentration as well as the Shannon’s diversity index reflecting both species richness and evenness in the JLE. The lowest Shannon index was observed in the SCS. However, the anammox bacterial species richness was greatest in the CJE. Candidatus Scalindua was the predominant anammox bacteria identified in the coastal sediments, especially in the SCS sediments. Candidatus Brocadia and Candidatus Kuenenia were more abundant in the estuarine sediments, particularly in JLE, than in the SCS. Phylogenetic analysis revealed distinct differentiation among Candidatus Scalindua, Candidatus Brocadia, and Candidatus Kuenenia, with the former exhibiting a greater level of diversity. There was significant spatial heterogeneity in the anammox bacteria across the four regions, characterized by distinct distribution patterns for rare species. Low-abundance (rare) bacteria thrived in their native habitats, whereas abundant taxa displayed greater dispersal capabilities. An analysis of the community assembly mechanism suggested that ecological drift predominantly shaped the overall anammox bacterial community in the coastal sediments. Rare species were more susceptible to dispersal limitations and environmental selection. Co-occurrence network analysis identified Candidatus Scalindua as a keystone genus and highlighted that rare species may play a crucial role in maintaining the ecological stability of the anammox bacterial community in coastal sediments.

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.